Respuesta :

The common base that can be used to rewrite each side of the equation is 2.

How to find the common base used to rewrite each equation?

The common base that can be used to rewrite each side of the equation is as follows:

2ˣ⁺³ - 3 = 5

add 3 to both sides

2ˣ⁺³ - 3 + 3 = 5 + 3

2ˣ⁺³ = 8

Hence,

2ˣ⁺³ = 2³

Therefore, the common base that can be used to rewrite each side of the equation is 2.

learn more on equation here: https://brainly.com/question/12025424

#SPJ1

Ver imagen vintechnology
ACCESS MORE